2013
DOI: 10.1371/journal.pone.0078552
|View full text |Cite
|
Sign up to set email alerts
|

Implications of False Negative and False Positive Diagnosis in Lymph Node Staging of NSCLC by Means of 18F-FDG PET/CT

Abstract: BackgroundIntegrated 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) is widely performed in hilar and mediastinal lymph node (HMLN) staging of non-small cell lung cancer (NSCLC). However, the diagnostic efficiency of PET/CT remains controversial. This retrospective study is to evaluate the accuracy of PET/CT and the characteristics of false negatives and false positives to improve specificity and sensitivity.Methods219 NSCLC patients with systematic lymph node dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…NSCLC is vulnerable to surgery unless it is not beyond N 2 lymph nodes. All patients possessing intrapulmoner lesions without LN metastasis (N 0 ) or ipsilateral hiler nodes (N 1 ) can be treated surgically [2]. If N 2 lymph node is positive, neoadjuvant chemotherapy with/without surgery or chemoradiotherapy is proper [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NSCLC is vulnerable to surgery unless it is not beyond N 2 lymph nodes. All patients possessing intrapulmoner lesions without LN metastasis (N 0 ) or ipsilateral hiler nodes (N 1 ) can be treated surgically [2]. If N 2 lymph node is positive, neoadjuvant chemotherapy with/without surgery or chemoradiotherapy is proper [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic efficiency is still keeping controversy because of lots of mostly benign pathologies stemming and rooting around this region by decreasing specificity creating false positive results [2]. Many of them are solitary and out of reach by ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, studies with <100 patients were excluded to secure study quality. As shown in Table , seven reports have documented the usefulness of primary tumor SUVmax for the risk stratification of mediastinal ONM using a variety of cut‐off values . Li et al showed that tumor size and primary tumor SUVmax were independently associated with mediastinal ONM in patients with clinical stage I NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…Though there is data to support the use of ultrasound echo‐texture characteristics to differentiate between malignant and benign lymph nodes, lymph nodes that are 0.5 cm or greater in short‐axis diameter on EBUS analysis should be considered for transbronchial needle aspiration (TBNA). Thorough evaluation of bilateral hila and mediastinum should be performed during the EBUS evaluation in light of the false‐negative rate of nuclear and radiologic staging . EBUS‐BNA of enlarged mediastinal/hilar lymph nodes should be performed in a systematic fashion, bearing in mind the laterality of the suspected primary lung lesion.…”
Section: Introductionmentioning
confidence: 99%